Efektivitas Tata Kelola Wakaf Nazir Organisasi: Pengalaman Majelis Wakil Cabang Nahdlatul Ulama Kecamatan Siman Ponorogo - Ni'matul Fauziyyah; Khairil Umami (Fakultas Syariah Institut Agama Islam Negeri Ponorogo, 2021)
This study aims to determine the effectiveness of the duties and authorities of the nazir organization in MWC NU Siman Ponorogo District in the management, maintenance and utilization of mosque and prayer room waqf in Siman Ponorogo District in terms of the Perspective of Law no. 41 of 2004 concerning Waqf. The type of research conducted by the author is a field research using qualitative methods. Data collection techniques were carried out using interviews and documentation. From this research, it is found that: 1) Nazir's organization in MWC NU, Siman District, Ponorogo Regency has been effective in carrying out his duties as stated in Law no. 41 of 2004 concerning waqf, but in terms of supervision there are still shortcomings. 2) The authority of Nazir organization in MWC NU Siman District in the management, maintenance and utilization of mosque and prayer room waqf in Mangunsuman Village according to Law no. 41 of 2004 concerning Waqf has so far been appropriate, namely in carrying out its duties and authorities in collaboration with the NU Branch, the takmir of the mosque waqf and the takmir of the musala waqf of Mangunsuman Village.